(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This research paper provides preliminary findings on views expressed by users regarding the use of Electronic Patient Journey Boards (EPJBs) in Queensland Health. Initial data were collected through a qualitative approach in order to understand the views of health professionals regarding EPJBs. This was achieved through interviews, brainstorming sessions and focus groups held with healthcare professionals who have used the EPJB and those who will be using EPJBs in the future. These qualitative data were analysed through the lens of three key critical variables, namely people, processes and technology. The preliminary findings show that these three variables are critical for the success of the use and implementation of EPJBs in the healthcare domain. Furthermore, this research paper was also able to identify factors that will have a significant influence on the implementation of a technology in a healthcare setting. This study is limited t o Queensland Health and needs further research to test the findings of the study, in order to apply the findings more generally. The analysis of data provides an initial blueprint for the implementation of EPJBs more widely.